1994
DOI: 10.1021/bi00189a034
|View full text |Cite
|
Sign up to set email alerts
|

Arsenate Reductase of Staphylococcus aureus Plasmid pI258

Abstract: Arsenate reductase encoded by Staphylococcus aureus arsenic-resistance plasmid pI258 was overproduced in Escherichia coli and purified. The purified enzyme reduced radioactive arsenate to arsenite when coupled to thioredoxin, thioredoxin reductase, and NADPH. NADPH oxidation coupled to arsenate reduction also required thioredoxin and thioredoxin reductase. Glutaredoxin and reduced glutathione did not stimulate arsenate reduction. NADPH oxidation showed Michaelis-Menten kinetics with a Km of 1 microM AsO4(3-) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
128
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(135 citation statements)
references
References 16 publications
5
128
2
Order By: Relevance
“…Pentavalent arsenic is transported into cells via phosphate transport systems in both prokaryotes (5) and eukaryotes (6). It is reduced to the more toxic trivalent arsenite by arsenate reductases (7)(8)(9). Arsenite can be detoxified either by extrusion from cells or by sequestration within intracellular organelles as thiol conjugates (3,4,10).…”
mentioning
confidence: 99%
“…Pentavalent arsenic is transported into cells via phosphate transport systems in both prokaryotes (5) and eukaryotes (6). It is reduced to the more toxic trivalent arsenite by arsenate reductases (7)(8)(9). Arsenite can be detoxified either by extrusion from cells or by sequestration within intracellular organelles as thiol conjugates (3,4,10).…”
mentioning
confidence: 99%
“…Several families of ArsC have been identified and characterized (10 -14). Among these, Staphylococcus aureus ArsC has been extensively studied (8,(15)(16)(17)(18)(19)(20)(21). These studies revealed that three redox active cysteine residues (Cys 10 , Cys 82 , and Cys 89 ) are critical for arsenate reduction.…”
mentioning
confidence: 99%
“…The conserved CX 5 R anion-binding motif containing Cys 10 , known as the P-loop, is proposed to be the arsenate-binding site (23). Four cysteine residues (Cys 10 , Cys 15 , Cys 82 , and Cys 89 ) are conserved between the two ArsC proteins.…”
mentioning
confidence: 99%
“…We have been able to successfully use the NPA-pKa correlation to determine the origin of the pKa perturbation of Nterminal cysteines in a-and 3 10 -helices, 12 in the study of the activation of the nucleophilic thiolates in the reaction catalyzed by arsenate reductase (ArsC) 13 and during mixed disulfide complex dissociation of ArsC and Trx. 11 In the conserved active site sequence motif Trp28-Cys29-Gly30-Pro31-Cys32 of Trx, we have studied the reactivity of Cys29 and Cys32 towards oxidized ArsC, 14,15 an endogenous substrate of Trx. Trx reduces oxidized ArsC via the formation of a mixed Trx-ArsC disulfide complex 16 (Fig.…”
Section: Introductionmentioning
confidence: 99%